FIGURE 3 in Rhinonyssus nenecoi sp. nov. (Mesostigmata: Rhinonyssidae); a new nasal mite from Daption capense (Procellariiformes: Procellariidae) ... - Gastal, Silvia Bainy; Mascarenhas, Carolina Silveira; Bugoni, Leandro (Zenodo, 2023)
FIGURE 3. Ventral view of Rhinonyssus nenecoi sp. nov. female. ... : Published as part of Gastal, Silvia Bainy, Mascarenhas, Carolina Silveira & Bugoni, Leandro, 2023, Rhinonyssus nenecoi sp. nov. (Mesostigmata: Rhinonyssidae); a new nasal mite from Daption capense (Procellariiformes: Procellariidae), pp. 269-276 in Zootaxa 5301 (2) on page 272, DOI: 10.11646/zootaxa.5301.2.7, http://zenodo.org/record/8030371 ...